Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0249232
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency of relapse for severe acute malnutrition and associated factors among under five children admitted to health facilities in Hadiya Zone, South Ethiopia

Abstract: Background Severe acute malnutrition is a common cause of morbidity and mortality among under five children in Ethiopia. A child may experience more than one episode of SAM depending on the improvement of the underlying factors. However, there is no study that determined the frequency of relapse of SAM cases after discharge in Ethiopia. Objective To identify the frequency of relapse and associated factors among children discharged after undergoing treatment for SAM in Hadiya Zone, South, Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 9 publications
4
14
4
Order By: Relevance
“…Older children were at lower risk of relapse in line with recent evidence from Ethiopia (Lambebo et al, 2021). Older children may be protected from relapse due to fewer nutritional and health problems often associated with improper introduction of complementary foods in younger children (Lambebo et al, 2021). In terms of case characteristics, our results showed that season of discharge predicted SAM relapse and postdischarge hospitalisation.…”
Section: Discussionsupporting
confidence: 87%
“…Older children were at lower risk of relapse in line with recent evidence from Ethiopia (Lambebo et al, 2021). Older children may be protected from relapse due to fewer nutritional and health problems often associated with improper introduction of complementary foods in younger children (Lambebo et al, 2021). In terms of case characteristics, our results showed that season of discharge predicted SAM relapse and postdischarge hospitalisation.…”
Section: Discussionsupporting
confidence: 87%
“…This may be due to differences in study design and population as a study conducted in Nigeria was a prospective cohort conducted for only 6 months, while the present study captured data over 5 years of the retrospective cohort, which may result in differences. In the present study, the overall relapse rate of SAM was found to be10.8% (95% CI 8.3; 12.6) which is consistent with the finding in the Hadya zone, Ethiopia [ 4 , 5 ]. This may show the commonality of the problem in our country, where the home environment is not usually altered although the child is treated for SAM in the health facility, which could lead to relapse of SAM.…”
Section: Discussionsupporting
confidence: 91%
“…Possibly early discharge form an inpatient treatment programs by using weight as discharge criteria from the treatment centers; they may have early weight gain as a remnant of nutritional edema-related weight. As nutritional edema affects the function of the glycocalyx is dependent upon sulfated proteoglycans and other glycosaminoglycans fundamentally related to a defect in sulphur metabolism, which can explain all clinical features of the condition, including the re-formation of edema [ 2 , 5 , 15 ]. The probability of getting readmission was increased for cases being a member of rural residents and the finding in our report show that being children resident in a rural setting were 5.3(AHR 5⋅3 = 95% CI 2⋅95, 13⋅87, p = 0.021) times the increased the hazard of SAM relapse as compared with their peers do live in an urban setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of anemia and death has also been reported by others in Gondar [2], Nekemte referral hospital [27], and in South Africa had (2.5-fold risk) [28]. A child may experience more than one episode of SAM, depending on the improvement of the underlying factors during inpatient treatment [29], but if re-admitted with a relapse, then the risk of death is doubled. Other factors that may be important in our setting include serving a poor pastoralist community, delayed presentation, lack of maternal participation in feeding programs, over prescription of intravenous therapies, early discontinuation of treatment due to insufficient financial means [2], and poor adherence of WHO SAM treatment guidelines [11,30].…”
Section: Plos Onesupporting
confidence: 59%